E-recruitment Tiered Architecture in Feasibility Study Role - Kamaran Hama Ali. A, Faraj (International Journal of Computer Sciences and Engineering, 2025)
One of the very important complement for feasibility study after log to connect to the recruitment management process is refers to study of feasibility in order to find out it’s feasible or not! For example; Traditional recruitment (TR) is not as feasible as the one tier architecture (1TA) recruitment due to the unordinary problematic-output results of TR and hazard create to health and safety. 1TA recruiting is computerized but it is run over dump-client/server based connection and the output result is better than TR, but its again not optimized output results. Nevertheless the intelligent-client/server based connection over (2TA, 3TA and NTA) systems are more feasible then the 1TA as simplicity- output results with excellent time-consume, while the personal computers (PCs) become more popular and powerful as smart terminals. Hence, the today’s users (especially youngster society) neither satisfied with the TR processes nor 1TA recruitment processing. After problem identifying and going toward to feasibility study to sort out of: What feasibility study type used from the TELOS (TELOS: five factors are collectively known as Technology, Economic, legal, operational, and Schedule) to achieve recruitment system over tiered architecture? But another important factor as a new contribution in this paper are used namely quality of output in the respect of time-consume by response time in mille-seconds measurement unit. Both Two tier architecture (2TA) and three tier architecture (3TA) are more feasible than the 1TA and TR due to implantation of feasibility study with those five factors been mentioned and some other factors. In this paper, the quality of output and Design architecture of the system are another factor for deciding the level of system feasible. There is a direct relation between (output result and Design architecture) with feasibility study. The five mentioned factors are working collectively for providing better output result time. This paper shows the role of feasibility study in Tiered architecture design by response time or load time recruitment system.